Biological heart rate reduction through genetic suppression of gαs protein in the sinoatrial node - Lugenbiel, Patrick; Bauer, Alexander; Kelemen, Kamilla; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Journal of the American Heart Association, 2012)
Background Elevated heart rate represents an independent risk factor for cardiovascular outcome in patients with heart disease. In the sinoatrial node, rate increase is mediated by β1 adrenoceptor mediated activation of the Gαs pathway. We hypothesized that genetic inactivation of the stimulatory Gαs protein in the sinoatrial node would provide sinus rate control and would prevent inappropriate heart rate acceleration during β-adrenergic activation. Methods and Results Domestic pigs (n=10) were evenly assigned to receive either Ad-small interfering RNA (siRNA)-Gαs gene therapy to inactivate Gαs or adenovirus encoding for green fluorescent protein (Ad-GFP) as control. Adenoviruses were applied through virus injection into the sinoatrial node followed by epicardial electroporation, and heart rates were evaluated for 7 days. Genetic inhibition of Gαs protein significantly reduced mean heart rates on day 7 by 16.5% compared with control animals (110±8.8 vs 131±9.4 beats per minute; P<0.01). On β-adrenergic stimulation with isoproterenol, we observed a tendency toward diminished rate response in the Ad-siRNA-Gαs group (Ad-siRNA-Gαs, +79.3%; Ad-GFP, +61.7%; n=3 animals per group; P= 0.294). Adverse effects of gene transfer on left ventricular ejection fraction (LVEF) were not detected following treatment (LVEFAd-siRNA-Gαs, 66%; LVEFAd-GFP, 60%). Conclusions In this preclinical proof-of-concept study targeted Ad-siRNA-Gαs gene therapy reduced heart rates during normal sinus rhythm compared with Ad-GFP treatment and prevented inappropriate rate increase after β-adrenergic stimulation. Gene therapy may provide an additional therapeutic option for heart rate reduction in cardiac disease. (J Am Heart Assoc. 2012;1:e000372 doi: 10.1161/JAHA.111.000372)
Gesehen am 11.06.2018
Der Buchstabe s ist im Titel tiefergestellt